THE EFFECT OF ESG DISCLOSURE ON FIRM VALUE: THE MODERATING ROLE OF MEDIA ATTENTION - Lenny Puspita Sari; Insyirah Putikadea (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the effect of ESG disclosure on firm value and to analyze the moderating role of media attention. Using panel data from 22 energy sector firms listed on the Indonesia Stock Exchange during 2022–2024, this research applies a purposive sampling technique and employs a Random Effects Model for regression analysis. Firm value is measured using Tobin’s Q, ESG disclosure is proxied by a GRI-based index, and media attention is measured using the natural logarithm of news coverage. The findings indicate that ESG disclosure has a positive but marginally significant effect on firm value, suggesting limited value relevance. Furthermore, media attention does not significantly moderate the relationship, indicating that external information dissemination has not been fully interpreted by investors as a credible signal. This study contributes by incorporating media attention as an external moderating variable and providing empirical evidence from the Indonesian energy sector.